2018
DOI: 10.1111/aji.13068
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferons differentially modulate maternal host immunity to infection by Listeria monocytogenes and Salmonella enterica serovar Typhimurium during pregnancy

Abstract: Problem: IFN-alpha receptor deficiency (IFNAR−/−) enhances immunity to Listeria monocytogenes (LM) and Salmonella enterica serovar Typhimurium (ST) in the non-pregnant state by inhibiting pathogen-induced immune cell death. However, the roles of IFNAR signaling in modulating immunity to infection during pregnancy are not well-understood. Method of Study: WT and IFNAR−/− mice were infected systemically with LM or ST. Bacterial burden in spleen and individual placentas was enumerated at day 3 post-infection. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
(65 reference statements)
0
13
0
Order By: Relevance
“…We previously showed in our intravenous infection model that the protection conferred by IFNAR1 deficiency against S . Tm in the non‐pregnant state was abrogated during pregnancy 49 . This was associated with decreased serum expression of pro‐inflammatory IL‐12p70 compared to non‐pregnant controls, suggesting a role for the cytokine in the control of systemic and placental infection during pregnancy.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We previously showed in our intravenous infection model that the protection conferred by IFNAR1 deficiency against S . Tm in the non‐pregnant state was abrogated during pregnancy 49 . This was associated with decreased serum expression of pro‐inflammatory IL‐12p70 compared to non‐pregnant controls, suggesting a role for the cytokine in the control of systemic and placental infection during pregnancy.…”
Section: Resultsmentioning
confidence: 96%
“…In particular, fetal survival was enhanced in infected pregnant IFNAR1 −/− mice. The contrasting clinical response following intravenous versus oral infection during pregnancy in IFNAR1 −/− mice suggests that the threshold of systemic infection can determine maternal susceptibility 49 . Following oral infection, as initially fewer bacteria enter the systemic circulation, the resistance conferred by IFNAR1 deficiency can be retained even in pregnant mice.…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in cell death improved the outcome in Ifnar -/mice infected with Salmonella enterica serovar Typhimurium [70,71], and recent work showed that the absence of STAT2-dependent type I IFN signaling led to decreased reactive oxygen species (ROS) production by neutrophils and disruption of hypoxia in the intestinal epithelium, causing inhibition of respiration in S. Typhimurium and impaired luminal expansion [72], suggesting that type I IFN signaling is beneficial for the bacterium, in this context. However, a unique study recently examined the influence of pregnancy on the outcome of infection with L. monocytogenes and S. Typhimurium in the presence and absence of type I IFN.…”
Section: Dual Effects Of Type I Ifn Signaling On Infection Outcomesmentioning
confidence: 99%
“…While pregnancy did not influence the detrimental outcome conferred by type I IFNs in L. monocytogenes infection, the protection afforded in Ifnar -/mice to S. Typhimurium infection was lost in pregnant mice. The compromised outcome to Salmonella infection in pregnant mice was attributed to decreased production of several cytokines, including IFN-γ, TNF, MCP-1, and IL-12 [70].…”
Section: Dual Effects Of Type I Ifn Signaling On Infection Outcomesmentioning
confidence: 99%
“…Similarly, IFN-I are induced in mice infected with Gram-positive bacteria, such as Group B streptococcus and Listeria monocytogenes . In these cases, IFN-I are protective as evidenced by a higher susceptibility to infection in IFNAR −/− mice compared to WT (119122). On the other hand, IFN-I play a deleterious role during infection with other pathogens by promoting dysregulated inflammation and host cell death.…”
Section: Intracellular Innate Immune Surveillance In Ehrlichiosismentioning
confidence: 99%